Pasantías en modelos de parcela demostrativa comunitaria para desarrollar capacidades técnicas de cultivo agroecológico del café en estudiantes del 2do grado de secundaria del Centro Poblado de Buenos Aires, distrito de Moyobamba - Saucedo Carranza, Ronald David (2013)
This research was aimed at showing the development of the technical capabilities of agroecological cultivation of the coffee through the development of intemships in models of demonstration parcel in students of the second grade of junior high school of the I. E. Cesar Vallejo- town ofBuenos Aires, 2012. The research was applied, experimental level, of pre-experimental design with the implementation ofpretest- post-test"with a single group, consisting ofa study sample of 30 students, the data were collected by applying the research tool called: Test to evaluate technical capabilities of agroecological coffee cultivation in students of the second grade of junior high school the inhabited center of Buenos Aires, Moyobamba district, San Martin region. The data were processed using frequency distribution and the T Student , to compare the results, it was found that prior to the development of the traineeships in models of demonstration coffee plots to develop the skills of cultivation agroecological the students were in a process of beginning and later, It was determined that his achievement ofprogramming was increased by 13.33% stressed, 63.33% achieved and a 2333 process, confirmed that the development of intemships in demonstration plots of coffee has influenced the learning of students in the second degree of the I. E. Cesar Vallejo- Buenos Aires. Key words: T Student, pretest- post-test.